RNAiSeq: How to See the Big Picture - Oppert, Brenda (Front Microbiol, 2019)
Targeting genes via RNA interference (RNAi) has become a successful method to reduce pest populations. Ideally, the expression of a gene critical for a life function in the insect is targeted by specific dsRNA, via spray or oral delivery. Experts have developed working guidelines in the development and regulation of RNAi as a pesticide. We argue that an important tool in the validation of RNAi is genome-wide expression analysis in the targeted pest, and we name this approach RNAiSeq. We have used RNAiSeq in the coleopteran model Tribolium castaneum to validate knockdown of target genes, and to examine the effect of knockdown on other genes. With RNAiSeq, we identified compensation responses to the knockdown of a gene encoding a major digestive enzyme in larvae that correlated to the responses we have observed with ingested protease inhibitors. Compensation can mask RNAi phenotypic responses and is important to understand in the context of efficacy. RNAiSeq also has identified new gene interactions that were previously unassociated with the target gene, important in the context of the large number of genes without associated functions in insects and other organisms. We discuss other research where RNAiSeq has led to important findings. These data not only provide validation of target knockdown, but also further identify changes in the expression of other genes impacted by the knockdown. From the context of pest control, this information can be used to predict genetic changes that will impact the efficacy of RNAi products in target pests.